Letter - Araquistain, Luis, 1886-1959
1940-11-13 013-0068-002 at present between Great Britain and Spain and how difficult for the British Ambassador to Madrid must be to intervene to plead humanly against a murder which will be covered with the mantle of legality. But if there is a case on which it is justified to break the diplomatic reserve and that the British Labour is morally bound to bring to bear the strongest pressure upon the British Embassy on Spain, this is, I think, one of the most signal occurrences. If Largo Caballero is let to be executed without doing the utmost from England to prevent it, I am afraid the cause of democracy will suffer tremendously in the eyes of the Spanish and South-American working class, the help of which may be still needed before the war is finished. Hoping to have your powerful assistance in this so full of anguish occasion, I am yours sincerely, Luis Araquistain 292/946/13/68(ii)